LAPORAN KASUS: PENGGUNAAN PROPOFOL DOSIS 10 MG/KG BERAT BADAN SECARA INTRAVENA SEBAGAI AGEN ANESTETIK DALAM PROSEDUR KASTRASI KUCING - Handoko, Jully (VITEK : Bidang Kedokteran Hewan, 2024)
Orchiectomy is one of the surgical procedures commonly performed in veterinary medicine. The procedure is to stop reproductive ability in male cats and mostly recommended by small animal medical practitioner to improve feline health and welfare. Orchiectomy is catagorized into short surgery and does not require a long anesthetic turnover. The choice of anesthetic agent is decided on the basis of safety considerations, in the sense that the patients do not need to be anesthetized for too long. In this case report, three feline patients (X, Y, Z) were administered with propofol at a dose of 10 mg per kg body weight intravenously. Premedications are performed 15 minutes prior to anesthesia by administering sulfate atropine at a dose of 0.05 mg per kg body weight subcutaneously and enrofloxacin 0.05 mg per kg body intramuscularly. Clinical signs observed in the patients included tongue-licking behavior during injection of propofol (all cats), heading down at the second minute (all cats), duration of sleep between 30-75 minutes, sign of pain during scrotal skin incision (cat Z), muscular tremors (cat X), decrease of rectal temperature (all cats), muscular rigidity during recovery (cat Z), vomiting after consciousness (no cats) and ataxia during the recovery (cat X and cat Z). The all observed clinical presentations show that propofol is sufficient and feasible to administer as an anesthetic or hypnotic for short surgical procedures, particularly in orchiectomy procedure in feline patients. Keywords: propofol, anesthetic, 10 mg/kg, kucing